2019
DOI: 10.1109/twc.2019.2911508
|View full text |Cite
|
Sign up to set email alerts
|

High-Mobility Wideband Massive MIMO Communications: Doppler Compensation, Analysis and Scaling Laws

Abstract: In this paper, we apply angle-domain Doppler compensation for high-mobility wideband massive multi-input multioutput (MIMO) uplink transmission. The time-varying multipath channel is considered between high-speed terminal and static base station (BS), where multiple Doppler frequency offsets (DFOs) are associated with distinct angle of departures (AoDs). With the aid of the large-scale uniform linear array (ULA) at the transmitter, we design a beamforming network to generate multiple parallel beamforming branc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 36 publications
1
55
0
Order By: Relevance
“…By exploiting the angle information of users, the carrier frequency offset (CFO) was estimated for each user individually through a joint spatial-frequency alignment procedure. Moreover, the authors in [121] and [122] addressed the joint estimation issue of Doppler shifts and CFO in high-mobility downlink massive MIMO systems, where a high-resolution beamforming network was designed to separate different Doppler and CFOs in the angle domain.…”
Section: Synchronizationmentioning
confidence: 99%
“…By exploiting the angle information of users, the carrier frequency offset (CFO) was estimated for each user individually through a joint spatial-frequency alignment procedure. Moreover, the authors in [121] and [122] addressed the joint estimation issue of Doppler shifts and CFO in high-mobility downlink massive MIMO systems, where a high-resolution beamforming network was designed to separate different Doppler and CFOs in the angle domain.…”
Section: Synchronizationmentioning
confidence: 99%
“…Hence, they all attain the maximum atω = 0. Apart from this, the following observations (22), (24) and (26) (26)).…”
Section: B Impact Of Beamforming Directions and Antenna Spacing On Cmentioning
confidence: 83%
“…• Explicit PSD expression with wider applicability and clearer insights: Unlike [23], [24] where the channel PSD is approximatively derived, we demonstrate that the channel PSD can be exactly expressed as the product of a pattern function and a beam-distortion function. The former can be uniquely determined by the antenna spacing and in fact corresponds to the radiation pattern of ULA, while the latter depends on how the beamforming directions are configured.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…time-varying channel estimation. On the other hand, for uplink high-mobility transmission, it has been demonstrated that the harmful effect of Doppler shift can be mitigated by massive MIMO technique [10]. Owing to the angle-domain Doppler shifts compensation technique, the asymptotic scaling law in [10] showed that, the Doppler spread decreases approximately as 1/…”
Section: Introductionmentioning
confidence: 99%